Metal Vapor Lasers with Modified Kinetics Pumped by a Capacitively Coupled Discharge; XVII International Symposium on Gas Flow and Chemical Lasers and High Power Laser Conference, 15-19 September 2008, Lisbon, Portugal - Gubarev F. A. Fedor Aleksandrovich; Evtushenko G. S. Gennady Sergeevich; Sukhanov V. B. Viktor Borisovich; Fedorov Valeriy F. (2008, 2008)
The paper presents the results of experimental study of CuBr+Ne+HBr – laser excited by a capacitively coupled discharge. It is shown that capacitive discharge can be successively applied for pumping of lasers on self-terminated transitions in metal vapors including metal vapor lasers with modified kinetics.